2017
DOI: 10.1016/j.rbmo.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Empty follicle syndrome revisited: definition, incidence, aetiology, early diagnosis and treatment

Abstract: In this review, the definition, incidence and possible causes of empty follicle syndrome (EFS), including molecular mechanisms that may underlie the syndrome, are discussed, along with prevention and treatment options. EFS is the complete failure to retrieve oocytes after ovarian stimulation, despite apparently normal follicle development and adequate follicular steroidogenesis. Two variants of EFS have been described: the 'genuine' form (gEFS), which occurs in the presence of adequate circulating HCG levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 48 publications
2
32
0
8
Order By: Relevance
“…The prevalence of all EFS is estimated to be 0.045% to 3.4% and of genuine EFS to be 0% to 1.1% ( 148 ). Some units will conduct a urine test for hCG (signifying a level of at least 10 to 20 IU/L) or a serum LH level following GnRHa to indicate whether EFS is genuine or false as a result from a problem with administration or absorption ( 149 ).…”
Section: Endocrine Requirements For Oocyte Maturation and Ovulationmentioning
confidence: 99%
“…The prevalence of all EFS is estimated to be 0.045% to 3.4% and of genuine EFS to be 0% to 1.1% ( 148 ). Some units will conduct a urine test for hCG (signifying a level of at least 10 to 20 IU/L) or a serum LH level following GnRHa to indicate whether EFS is genuine or false as a result from a problem with administration or absorption ( 149 ).…”
Section: Endocrine Requirements For Oocyte Maturation and Ovulationmentioning
confidence: 99%
“…Interestingly, Revelli et al suggested that EFS might not be a constant condition. Thus, in a study of 43 patients undergoing a second stimulation after EFS in the first cycle, a total of 37 patients (86%) obtained MII oocytes, although the stimulation protocols were similar, and a hCG trigger was used for the second cycle too (32). This could be caused by cycle-to-cycle variations in oocyte quality.…”
Section: Empty Follicle Syndrome Following Hcg Triggermentioning
confidence: 99%
“…However, only in a few cases, there is a complete failure to retrieve oocytes after hCG as well as the GnRHa trigger (1,2). In the case of a GnRHa trigger, failure to retrieve mature oocytes should not always be classified as an Empty Follicle Syndrome (EFS) (3), as the pathophysiology is likely to be different. Based on the available literature, some authors do not support the existence of the EFS, considering the "syndrome" due to errors in the administration of the trigger.…”
Section: Introductionmentioning
confidence: 99%